HUMAN CAPITAL AND OCCUPATIONAL SEGREGATION IN INDONESIA: A STUDY BY GENDER AND SECTORS OF EMPLOYMENT - SRI SUSILOWATI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2004)
The objective of this study is to examine the patters of employment differentials separately for women and men in Indonesian labour market. This study uses the data from the 1993 Indonesian Family Life Survey (IFLS), a periodic joint survey which has been run by Lembaga Demografi, Faculty of Economic, University of Indonesia and RAND. Using logistic model, the result suggests that education is a particularly important of sector employment outcomes. Experience was also notably important in determining whether a male worker was in professional or in managerial and administrative occupation.